Information, technology, and market rewards: Incentivizing aflatoxin control in Ghana - Magnan, Nicholas; Hoffmann, Vivian; Garrido, Gissele; Kanyam, Faniel Akwasi; Opoku, Nelson (International Food Policy Research Institute, 2019)
Food safety hazards threaten the health and market access of smallholder farming households. Smallholders face a number of barriers to improving food safety and quality, including low awareness, high input costs, and the failure of premium prices to pass through to producers. In this paper we examine how lifting these barriers affects Ghanaian groundnut farmers’ adoption of low-tech, low-cost post-harvest practices that reduce aflatoxin contamination. We conduct a randomized controlled trial in northern Ghana over the course of two seasons to test three interventions: (1) training on aflatoxin and its prevention, (2) distribution of free drying sheets, and (3) a price premium for groundnuts that comply with local aflatoxin regulations. In the first year we test for effects on post-harvest practices and aflatoxin levels, and in the second we test for effects on aflatoxin levels only. We find that training farmers substantially improves post-harvest practices. Drying sheet distribution and to a lesser extent the premium price lead to further improvements. We find substantial corresponding decreases in aflatoxin levels from drying sheet provision in the study region where background aflatoxin levels were highest. Beyond regional differences, benefits are higher for households with higher aflatoxin at baseline, more members, and young children. The estimated impacts of the price premium intervention are of similar magnitude, but not statistically significant.